2010
DOI: 10.4238/vol9-1gmr746
|View full text |Cite
|
Sign up to set email alerts
|

Genetic, embryonic and anatomical study of an interspecific cassava hybrid

Abstract: ABSTRACT. A molecular, anatomical and cytogenetic study of an interspecific hybrid between Manihot esculenta (cassava) and the wild species M. oligantha was carried out. Cytogenetics revealed relatively complete chromosome pairing and high viability of the pollen grains. Ovule structure examined by the clearing method showed polyembryony in 2.7% of the ovules. Doubling of the chromosome number resulted in an increase in polyembryony of up to 18% and a reduction in pollen viability. Multivalent formation was al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Non-articulated laticifers were identified in species described by Cunha Neto et al (2014). Nassar et al (2010a) observed laticifers articulated only in the phloem of the hybrids between M. esculenta and M. oligantha, as well as in M. glaziovii M€ ull. Arg.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Non-articulated laticifers were identified in species described by Cunha Neto et al (2014). Nassar et al (2010a) observed laticifers articulated only in the phloem of the hybrids between M. esculenta and M. oligantha, as well as in M. glaziovii M€ ull. Arg.…”
Section: Discussionmentioning
confidence: 85%
“…Nassar et al. () observed laticifers articulated only in the phloem of the hybrids between M. esculenta and M. oligantha , as well as in M. glaziovii Müll. Arg.…”
Section: Discussionmentioning
confidence: 99%
“…The quadratic equation, built for TEAA and TAA, revealed higher r 2 as the number of variables increased suggesting that the model is adequate. Among all the amino acids, tryptophan is the only variable predictor and one of the most common variables despite its hydrolysis during analysis (Nassar and Souza, 2007). Histidine and phenylalanine also occurred frequently for all the models, and this could be linked to the fact that they are essential amino acids that play vital roles in the biogenesis of proteins.…”
Section: Discussionmentioning
confidence: 98%
“…Although female gamete formation has been reported for L2 (Burge et al, 2002), there is evidence that L1 may be involved in apomictic embryo sac formation, besides L2 itself (Koltunow and Grossniklaus, 2003). Ploidy relationship and low frequencies of polyembryo sacs in cassava have been reported (Nassar et al, 2010;Freitas and Nassar, 2013).…”
Section: Discussionmentioning
confidence: 99%